Goal Management Training for rehabilitation of executive functions: a systematic review of effectivness in patients with acquired brain injury. (January 2014) - Krasny-Pacini, Agata; Chevignard, Mathilde; Evans, Jonathan
Abstract Purpose: To determine if Goal Management Training (GMT) is effective for the rehabilitation of executive functions following brain injury when administered alone or in combination with other interventions. Method: Systematic review, with quality appraisal specific to executive functions research and calculation of effect sizes. Results: Twelve studies were included. Four studies were "Proof-of-principle" studies, testing the potential effectiveness of GMT and eight were rehabilitation studies. Effectiveness was greater when GMT was combined with other interventions. The most effective interventions appeared to be those combing GMT with: Problem Solving Therapy; personal goal setting; external cueing or prompting apply GMT to the current task; personal homework to increase patients' commitment and training intensity; ecological and daily life training activities rather than paper-and-pencil, office-type tasks. Level of support for GMT was higher for studies measuring outcome in terms of increases in participation in everyday activities rather than on measures of executive impairment. Conclusion: Comprehensive rehabilitation programs incorporating GMT, but integrating other approaches, are effective in executive function rehabilitation following brain injury in adults. There is insufficient evidence to support use of GMT as a stand-alone intervention. Implications for Rehabilitation Goal Management Training (GMT) is a well-studied metacognitive intervention for executive dysfunction. Comprehensive rehabilitation programs relying partly on GMT and integrating other approaches are effective in executive function rehabilitation following brain injury in adults. GMT alone does not have sufficient evidence to support it as a training on its own.